Rural-Urban Linkages Pertaining to Manufacturing in Bangkok Mega-Urban Region: A Case Study of Pathum Thani Province - Sanit, Peamsook (Journal of Architectural/Planning Research and Studies (JARS), 2018)
The objective of the research is to study the linkages between rural and urban areas effecting on the production of small-scale manufacturing in rural area of Pathum Thani as part of the Northern Extended Bangkok Metropolitan Region. This study bases on the Forward and Backward Production Linkages concept. A survey is conducted by using questionnaire methods to gather data from entrepreneurs in the study area. The result of research finds that the rural small-scale manufacturing in the Northern Extended Bangkok Metropolitan Region mostly relate to Bangkok, a major city, in terms of flow of people and goods. In addition, there are other linkages between other cities located along the Phaholyothin Road, such as Rangsit, Muang Pathum Thani, and Khong Luang, extended to some parts of Phra Nakhon Sri Ayutthaya. Furthermore, the study finds that the Eastern Extended Bangkok Metropolitan Region along Bangna-Trad Road, covering Samut Prakan, Chon Buri, and Rayong provinces, is considerably significant to the rural small-scale manufacturing as well. As a result, it is concluded that the rural small-scale manufacturing in the study area has a connection with suppliers and customers in urban area located directly in both the Northern Extended Bangkok Metropolitan Region and the Eastern Extended Bangkok Metropolitan Region. It is suggested that there should be strategic plans for the administrative management of the extended metropolitan regions based on current trends to control the infrastructure development and to promote the important local manufacturing. Also, the potential of rural-urban linkages pertaining to manufacturing in both regions can be a guideline in order to efficiently develop a policy framework for the extended metropolitan region in the future.